1999
DOI: 10.1021/la990367l
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Chemical Calculations of the Charge Distribution in Ionic Surfactants

Abstract: The charge distribution in common ionic surfactant molecules is estimated using quantum chemical methods. Calculations are compared for four widely accepted semiempirical methods (MINDO/3, AM1, PM3, and MNDO/d). The atomic partial charges are calculated for surfactants with linear alkyl tails and common headgroups, including anionic (sulfate, sulfonate, carboxylate), cationic (trimethylammonium, pyridinium), and amphoteric (betaine, dimethylamine oxide) classes. The headgroup charges are shown to distribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 18 publications
6
92
0
1
Order By: Relevance
“…This result agrees with semiempirical computations of single anionic surfactants, and supports the view that the interior of self assembled structures made of SDS surfactants, e.g. micelles, may be polar 58 . An interesting consequence of these polarization effects would be and increase in the penetration of water and ions in the hydrophobic region of the NBF.…”
Section: Conclusion and Final Remarkssupporting
confidence: 88%
See 1 more Smart Citation
“…This result agrees with semiempirical computations of single anionic surfactants, and supports the view that the interior of self assembled structures made of SDS surfactants, e.g. micelles, may be polar 58 . An interesting consequence of these polarization effects would be and increase in the penetration of water and ions in the hydrophobic region of the NBF.…”
Section: Conclusion and Final Remarkssupporting
confidence: 88%
“…The possibility of charge transfer effects in these surfactants has been discussed before. Using first-principles computations it has been shown that anionic hydrocarbons such as SDS feature significant charge transfer, which extends from the head group to the terminal methyl group 57,58 . Semiempirical methods indicate that such charge transfer also occurs in normal alkanes, although in the case of dodecane, which is relevant to our system, the charge transfer results in charge separation in the two terminal methyl and methylene groups.…”
Section: Resultsmentioning
confidence: 99%
“…One is that the calculation is very complicate. For example, to the binary anionic/cationic system, A = CH 3 (CH 2 ) 11 The other difficulty is the determination of the position for each atom of the surfactants in space. It has been known that there are kinds of movements in a molecule such as the extension, compression, winding and rotation of all kinds bonds, the collision among atoms, and so on, and that those movements make the position of atoms can not be precisely determined and consequently the distance r ij in Lennard-Jones formula cannot be determined.…”
Section: Simplification Of the Calculation Of εmentioning
confidence: 99%
“…This conclusion is also supported by our simulation results. Although most of the models on ionic surfactants assume a point unit charge at the headgroup or counterion, quantum chemical methods unveiled that the charge can partially distribute to the rest of the molecule, more significantly on the α-methylene group and less on the remaining alkyl chain [31]. This charge distribution has an important effect on surfactant self-assembly and can explain the polarity of micelle cores.…”
Section: Introductionmentioning
confidence: 99%